2020
DOI: 10.1186/s12974-020-01942-x
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of the microglial Hv1 proton channel attenuates neuronal pyroptosis and inhibits inflammatory reaction after spinal cord injury

Abstract: Background: Spinal cord injury (SCI) causes neurological dysfunction with devastating consequences. SCI pathogenesis is accompanied by inflammasome activation and neuronal damage. But the spatial pattern and the time course of neuronal pyroptosis and apoptosis after SCI should be further elucidated. The microglial voltagegated proton channel (Hv1) is implicated in reactive oxygen species (ROS)-induced neuronal damage following ischemic stroke. However, there is a lack of quantification on the neuronal pyroptos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 45 publications
2
50
0
Order By: Relevance
“…114 In a recent study, the results showed that microglial voltage-gated proton channel deficiency could reduce NLRP3induced neuronal pyroptosis. 115 Furthermore, the neuroprotection of erythropoetin (EPO) against sevoflurane induced-neuronal pyroptosis is related to Erk1/2-Nrf2/Bach1 signal pathway. 116 A previous study demonstrated that S pneumoniae could induce pyroptosis in murine microglia and that NLRP3 inflammasome is critical for caspase-1 activation during pyroptosis.…”
Section: The Role Of Par Ap Tos Is and Pyrop Tos Is In S Pinal Cordmentioning
confidence: 99%
“…114 In a recent study, the results showed that microglial voltage-gated proton channel deficiency could reduce NLRP3induced neuronal pyroptosis. 115 Furthermore, the neuroprotection of erythropoetin (EPO) against sevoflurane induced-neuronal pyroptosis is related to Erk1/2-Nrf2/Bach1 signal pathway. 116 A previous study demonstrated that S pneumoniae could induce pyroptosis in murine microglia and that NLRP3 inflammasome is critical for caspase-1 activation during pyroptosis.…”
Section: The Role Of Par Ap Tos Is and Pyrop Tos Is In S Pinal Cordmentioning
confidence: 99%
“…We stabilized the spinal cord in a small animal spinal holder (RWD, Inc., China) by clamping the T8 and T11 vertebrae with stabilizing forceps. Spinal contusion injury was performed with a metal rod (10-g weight) dropped from a height of 25 mm onto the exposed dorsal surface of the spinal cord using a modified NYU impactor ( Li et al, 2020 ). After spinal contusion, the wound was rinsed with normal saline and sutured in layers.…”
Section: Methodsmentioning
confidence: 99%
“…This was confirmed in CD11b + microglia/macrophages isolated from the adult spinal cord at 3 days post-injury. In situ, cells immunoreactive for Hv1 coexpress ionized calcium-binding adaptor molecule 1 (Iba1), a known marker for microglia/macrophages (Li et al, 2020b). Furthermore, a nearly four-fold increase in Hv1 protein expression was observed in spinal cord tissue at 3 days post-injury (Li et al, 2021).…”
Section: The Temporal and Spatial Expression Of Hv1 In The Cnsmentioning
confidence: 99%